2013
DOI: 10.1038/bmt.2012.267
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity conditioning with fludarabine and thiotepa for second allogeneic transplantation of relapsed patients with AML

Abstract: A second allograft was offered to 58 relapsed AML patients after conditioning with fludarabine 90-150 mg/m 2 and thiotepa 15 mg/kg, in most cases with active disease. Median age was 53 years (range 23-69), median time to relapse after the first allo-SCT was 326 (47-2189) days and median follow-up was 6.7 years. GVHD prophylaxis consisted mainly of CsA and alemtuzumab. Response rates at 1 month were CR in 50 and persistent disease in 3/53 evaluable patients. At 3 years, the relapse incidence (95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…With a 3-year OS probability of 29%, survival resembles that reported for second allotransplants for relapsed myeloid malignancies, ranging from 21% after 2 years to 32% after 5 years. [10][11][12][13][14]18 Second allogeneic transplantation for lymphoma relapse K Horstmann et al Importantly, the 3-year NRM of 23% observed here compares well with NRM figures observed in registry studies on first allotransplants in lymphoma, 2,[19][20][21][22][23][24][25] implying that a repeat allotransplant does not seem to be associated with an unacceptable increase in NRM.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…With a 3-year OS probability of 29%, survival resembles that reported for second allotransplants for relapsed myeloid malignancies, ranging from 21% after 2 years to 32% after 5 years. [10][11][12][13][14]18 Second allogeneic transplantation for lymphoma relapse K Horstmann et al Importantly, the 3-year NRM of 23% observed here compares well with NRM figures observed in registry studies on first allotransplants in lymphoma, 2,[19][20][21][22][23][24][25] implying that a repeat allotransplant does not seem to be associated with an unacceptable increase in NRM.…”
Section: Discussionsupporting
confidence: 74%
“…Similar to leukemia, [10][11][12][13][14]18 the most important risk factors adversely affecting OS after alloHSCT_2 for lymphoma were remission status at second transplant and interval between alloHSCT_1 and alloHSCT_2 (as a surrogate marker for remission duration after alloHSCT_1). In contrast, selecting a donor for alloHSCT_2 different from that used for alloHSCT_1 had no significant impact on OS, PFS or RI in the patient sample studied here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Several other studies with shorter follow-up report results predicting 5-year survivals similar to those of the present study. [9][10][11][12][13][14] The moderate differences observed are likely to represent differences in the patient materials.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that in previous studies have consistently been shown to have prognostic utility for survival are disease status, 6,8,[10][11][12][13]15,16 interval between the first transplantation and relapse 5,8,[12][13][14]16 and age. [5][6][7][8]12,14,15,17 A longer interval from the first transplantation to relapse predicts better survival. The length of the remission after which the prognosis has been found clearly better has usually ranged between 6 months and 1 year.…”
Section: Discussionmentioning
confidence: 99%